IMPLEMENTASI METODE ROLE PLAY DALAM PEMBELAJARAN PAI DI SDN 057222 TAPAK KUDA - Sapridah (Journal of Community Devation, 2025)
Moral decline is a major problem facing the Indonesian nation today, including Aceh Province. Religious education is currently receiving sharp criticism because of its inability to address various important issues in society, many new problems are emerging so that its effective role is being questioned. Learning methods are needed that can prepare students to be able to understand, believe, be devout, have noble character and practice Islam from the sources of the Koran and Hadith through experience in a fun learning process. The aim of the research in this article is to find out the role play method in learning Islamic Religious Education (PAI) at SDN 057222 Tapak Kuda, and to find out the procedures for implementing role play in learning Islamic Religious Education (PAI) at SDN 057222 Tapak Kuda. A qualitative descriptive research approach was used in this research. Information collected through interviews, field observations and documentation. Data is reduced, presented, and conclusions are drawn during the data analysis process. The results of this research are that PAI learning using the role play method has made a real contribution to PAUD students by playing a direct role as imams, congregations and other congregations in optimizing educational development, increasing devotion to Allah SWT and producing an effective learning process and can become good graduates. competent, and the use of the role play method in PAI learning which is applied to learning at SDN 057222 Tapak Kuda has changed the new learning atmosphere and provided a different learning experience from previous material, thus forming participants educate to think more creatively and actively.